Poza antropocentryzm. Funkcje drugoosobowej zoonarracji w powieści Szczur Andrzeja Zaniewskiego - Piotr F. Piekutowski (Zagadnienia Rodzajów Literackich)
This paper presents a correlation between second-person narration and the more-than-human perspectivity in animal narratives. The analysis focuses on representations of “you” narration in Andrzej Zaniewski’s novel Rat, published for the first time in 1995. “Rat-centric” fiction, as Marco Caracciolo describes it, talks about various experiences of the title animal. Although the dominant diegetic form in the novel is the first-person narrative, the appearing parts of the text told from a second-person point of view turn out to be a significant element of a non-anthropocentric perspective. Considering the influence of form on the posthuman message, the paper is based on research in the field of animal studies and contemporary narratology, including, among others, Irene Kacandes’s “literary performative”, David Herman’s “double deixis” or Dominique Lestel’s “thinking with fur”. In this article, I propose to distinguish three functions of the second-person narrative in Rat: immersive, empathetic and identity roles. The immersive function participates in adapting a sensorimotor repertoire to the intersubjective perception of the non-human world. The second of them, the empathetic function, by bonding the human narratee with the animal character, opens a possibility of embodied co-experience and verification of anthropocentric norms. The third, identity function, participates in (de)constructing the rat selfhood. Findings of the proposed perspective of second-person zoonarration sheds new light on its formal opportunities for creating posthuman agency, thinking, and storytelling.